Malaysia France Institute and Advance Technology: A Case Study - See, Meng Liong (1998)
This case is about Malaysia French Institute (MFI) who at best experienced some difficulties in transferring French Technology in Malaysian market. Reference to the implementation process, MFI practiced French management Style and fully depend on French technology and specialist to offer training courses. Problem arose due to the adaptability and suitability of French methods in operating business activities. Adjustment had been done to suit the local employees whenever the management foresees the need of improvement. Involvement of this changes incurr large amount of expenses, even exceeded the revenue generated . Under these Circumstances, MFI have a lot of areas to improve. The areas involved as hereunder: i . Requirement of suitable organization structure in basic management function . ii. Specification of jobs function to each level of employees. iii. Developments of market planning to capture larger market share. iv. Appropriate planning on future expansion.